Genome-Wide RNA Polymerase II Profiles and RNA Accumulation Reveal Kinetics of Transcription and Associated Epigenetic Changes During Diurnal Cycles - Le Martelot, Gwendal; Canella, Donatella; Symul, Laura; Migliavacca, Eugenia; Gilardi, Federica; Liechti, Robin; Martin, Olivier; Harshman, Keith; Delorenzi, Mauro; Desvergne, Béatrice; Herr, Winship; Deplancke, Bart; et al. (PLOS Biology, 2012)
Genome-wide rhythms in RNA polymerase II loading and dynamic chromatin remodeling underlie periodic gene expression during diurnal cycles in the mouse liver.